2016
DOI: 10.1264/jsme2.me15209
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetically Diverse Aerobic Anoxygenic Phototrophic Bacteria Isolated from Epilithic Biofilms in Tama River, Japan

Abstract: The diversity of aerobic anoxygenic phototrophic (AAP) bacteria in freshwater environments, particularly in rivers, has not been examined in as much detail as in ocean environments. In the present study, we investigated the phylogenetic and physiological diversities of AAP bacteria in biofilms that developed on submerged stones in a freshwater river using culture methods. The biofilms collected were homogenized and inoculated on solid media and incubated aerobically in the dark. Sixty-eight red-, pink-, yellow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…Some of the previous studies reported the presence of the particle-attached AAnPB. Hirose et al [24] detected the AAnPB species in the epilithic biofilm of Tama River. Most of first cultures of AAnPB species were isolated from the surface of seaweed [25].…”
Section: Determination Of Absolute Cell Abundances Of the Total Bactementioning
confidence: 99%
“…Some of the previous studies reported the presence of the particle-attached AAnPB. Hirose et al [24] detected the AAnPB species in the epilithic biofilm of Tama River. Most of first cultures of AAnPB species were isolated from the surface of seaweed [25].…”
Section: Determination Of Absolute Cell Abundances Of the Total Bactementioning
confidence: 99%
“…Due to their pivotal roles in the biogeochemical cycle ( 19 , 35 ), the study of lotic ecology has been attracting increasing interest ( 24 , 42 , 54 ). In attempts to model ecological mechanisms in lotic ecosystems, bacteria are essentially viewed as primary contributors ( 41 , 47 ). Thus, the dynamics of a bacterial community along a river have received increasing attention.…”
mentioning
confidence: 99%
“…Polymorphobacter is capable of photosynthetic energy production (Hirose, Matsuura & Haruta, 2016). A previous study of bacterial communities in dust under different lighting conditions suggest that some bacteria can survive in enclosed systems, either as auxotrophs or by cannibalizing other members of the microbial community.…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%